2020
DOI: 10.1017/dmp.2020.132
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Preparedness Measures for Biological Hazards: A Systematic Review and Meta-Synthesis

Abstract: Background: Biological hazards are one of the most important and common types of hazards in emergencies and disasters. Hospital preparedness measures for biological hazards are essential for a proper response and mitigation of its effects. The aim of this systematic review is to investigate hospital preparedness measures for biological hazards. Methods: For this research, electronic databases including Web of Science, PubMed, ScienceDirect, Scopus, ProQuest, Google Scholar, and Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The emergence of new species of microorganisms, as well as the development of research techniques, causes new biological factors, which are occupational hazards, to be detected in the work environment. Important issues surrounding biological factors of occupational hazards for paramedics include, e.g., blood-borne viruses; new species of viruses (SARS-CoV-2), prions and bacteria, germs carried by ticks (in cases of carrying out work tasks in wooded areas); allergenic and immunotoxic factors of microbe, plant, and animal origin present in organic dust [20][21][22][23][24].…”
Section: Medical Professionmentioning
confidence: 99%
“…The emergence of new species of microorganisms, as well as the development of research techniques, causes new biological factors, which are occupational hazards, to be detected in the work environment. Important issues surrounding biological factors of occupational hazards for paramedics include, e.g., blood-borne viruses; new species of viruses (SARS-CoV-2), prions and bacteria, germs carried by ticks (in cases of carrying out work tasks in wooded areas); allergenic and immunotoxic factors of microbe, plant, and animal origin present in organic dust [20][21][22][23][24].…”
Section: Medical Professionmentioning
confidence: 99%
“…They also showed that managers' knowledge about hospital emergency preparedness and response was at an average level and a signi cant relationship was observed between the managers' knowledge and hospital emergency preparedness and response (22). Moreover, Bartley et al (2012) showed that an audiovisual presentation of hospital disaster plans followed by a simulated exercise and debrie ng improved staff knowledge, con dence, and hospital emergency preparedness and response (23). The present study showed that surge capacity training using an action research design had a positive impact on most components of hospital preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals have emergency preparedness plans in place, have practiced these plans regularly and have suffered far fewer injuries because of incidents, according to experience (Dowlati et al, 2020). Each hospital must have its unique program, which should include scenarios based on hospital risks.…”
Section: Discussionmentioning
confidence: 99%
“…Each hospital must have its unique program, which should include scenarios based on hospital risks. This program should be simulated and practiced in real-time and with practical assessment twice a year (Aminizadeh et al, 2019;Dowlati et al, 2020). In addition, developing biological threat scenarios and preparing the hospital's central HICS for periodic drills are required to improve the hospital's response system in biological disasters (Beyramijam et al, 2020;Esmail Heidaranlu et al, 2015) IJDRBE 13,2 Limitations One of the limitations of this article is the self-assessment of hospitals by the Secretary of the Hospital Risk Management Committee.…”
Section: Discussionmentioning
confidence: 99%